2021
DOI: 10.3390/ijms22041598
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Reconstitution of Human Lipoyl Synthase (LIAS) Supports ISCA2 and ISCU as Primary Cluster Donors and an Ordered Mechanism of Cluster Assembly

Abstract: Lipoyl synthase (LIAS) is an iron–sulfur cluster protein and a member of the radical S-adenosylmethionine (SAM) superfamily that catalyzes the final step of lipoic acid biosynthesis. The enzyme contains two [4Fe–4S] centers (reducing and auxiliary clusters) that promote radical formation and sulfur transfer, respectively. Most information concerning LIAS and its mechanism has been determined from prokaryotic enzymes. Herein, we detail the expression, isolation, and characterization of human LIAS, its reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…A study found that FDX1 can impact the prognosis of lung adenocarcinoma (Zhang et al, 2021). LIAS encodes lipoyl synthase, an Fe-S cluster protein and a member of the radical S-adenosylmethionine (SAM) superfamily, which is a vital component of the lipoic acid pathway (Hendricks et al, 2021). DLAT encodes dihydrolipoamide S-acetyltransferase (DLAT), which is a subunit of the pyruvate dehydrogenase (PDH) complex and a protein target of lipoylation.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that FDX1 can impact the prognosis of lung adenocarcinoma (Zhang et al, 2021). LIAS encodes lipoyl synthase, an Fe-S cluster protein and a member of the radical S-adenosylmethionine (SAM) superfamily, which is a vital component of the lipoic acid pathway (Hendricks et al, 2021). DLAT encodes dihydrolipoamide S-acetyltransferase (DLAT), which is a subunit of the pyruvate dehydrogenase (PDH) complex and a protein target of lipoylation.…”
Section: Discussionmentioning
confidence: 99%
“…LIAS is a member of the radical S-adenosylmethionine (SAM) superfamily [ 34 , 35 ]. It catalyzes the final step of the biosynthesis of lipoyl cofactor [ 36 , 37 , 38 ] and binds two [4Fe-4S] clusters [ 39 , 40 ]: a [4Fe-4S] cluster (FeS RS ), typical of all radical SAM enzymes, and a [4Fe-4S] cluster (FeS aux ) that provides two sulfur atoms to the lipoyl cofactor [ 41 , 42 ]. It has been shown that the C-domain of NFU1 drives first [4Fe-4S] 2+ cluster delivery from the ISCA1-ISCA2 complex, where the [4Fe-4S] 2+ cluster is assembled, to a [4Fe-4S] 2+ ISCA1-NFU1 intermediate complex, which then specifically directs the cluster into the FeS RS site of LIAS [ 32 , 33 ].…”
Section: [4fe-4s] Cluster Assembly In Mitochondriamentioning
confidence: 99%
“…Bert Vallee witnessed the early days of this metallomics research at the turn of the millennium, although he could no longer actively contribute to it. In his honour, Hendricks et al discuss the role and relevance of thiolate clusters of proteins in different taxonomic groups and report on such a controlled metal insertion procedure [24]. In their manuscript, they show the transfer of iron ions from the iron-sulfur cluster assembly proteins ISCA2 and ISCU to lipoyl synthase (LIAS) [24].…”
Section: The Special Issue On Special Thiophilic Metalsmentioning
confidence: 99%
“…In his honour, Hendricks et al discuss the role and relevance of thiolate clusters of proteins in different taxonomic groups and report on such a controlled metal insertion procedure [24]. In their manuscript, they show the transfer of iron ions from the iron-sulfur cluster assembly proteins ISCA2 and ISCU to lipoyl synthase (LIAS) [24]. This enzyme is responsible for the biosynthesis of lipoic acid, which has several important biological roles.…”
Section: The Special Issue On Special Thiophilic Metalsmentioning
confidence: 99%